2022
DOI: 10.3389/fcell.2021.734597
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen Synergy: An Emerging Route to Boosting Human Beta Cell Proliferation

Abstract: Decreased number and function of beta cells are a key aspect of diabetes mellitus (diabetes), a disease that remains an onerous global health problem. Means of restoring beta cell mass are urgently being sought as a potential cure for diabetes. Several strategies, such as de novo beta cell derivation via pluripotent stem cell differentiation or mature somatic cell transdifferentiation, have yielded promising results. Beta cell expansion is another promising strategy, rendered challenging by the very low prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 234 publications
(318 reference statements)
0
9
0
8
Order By: Relevance
“…With the exception of HG-9-91-01, these agents increase β-cell proliferation in physiological glucose 5,9,5154 , suggesting they circumvent feedback control of β-cell mass and could risk hypoglycemia if treatment is continued after the deficit in functional β-cell mass is corrected. Combination therapy with agents exhibiting synergism has been proposed as a strategy to maximize β-cell expansion 7 . Here, we found that SIRT2 regulates β-cell proliferation via a novel metabolic mechanism, opening the possibility for new combinatorial therapies utilizing distinct synergistic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of HG-9-91-01, these agents increase β-cell proliferation in physiological glucose 5,9,5154 , suggesting they circumvent feedback control of β-cell mass and could risk hypoglycemia if treatment is continued after the deficit in functional β-cell mass is corrected. Combination therapy with agents exhibiting synergism has been proposed as a strategy to maximize β-cell expansion 7 . Here, we found that SIRT2 regulates β-cell proliferation via a novel metabolic mechanism, opening the possibility for new combinatorial therapies utilizing distinct synergistic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating therapeutic targets for expanding b-cell mass have identified several compounds that stimulate proliferation of adult human b-cells [5][6][7][8] . Recent findings from several groups converged upon mechanisms involving inhibition of the kinase DYRK1A, with further increases of b-cell proliferation achieved using combination treatment with DYRK1A inhibitors and other agents including GLP1 6 or inhibitors of the TGFb pathway 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of beta cell mass is infrequent in adult humans, with an estimated rate of 0.1–0.5% proliferating cells versus a 4% peak in fetal development [ 83 , 84 , 85 ]. However, under conditions of stress and heightened insulin demand due to factors including excess calorie intake, insulin resistance, and pregnancy, not only beta cell function but also beta cell mass increases to compensate for an amplified insulin need [ 86 , 87 ]. Beta cell mass expansion can occur through a variety of mechanisms, including neogenesis, proliferation, and transdifferentiation ( Figure 2 ).…”
Section: Compensation: Beta Cell Proliferation Transdifferentiation A...mentioning
confidence: 99%
“…Increasing insulin secretion in response to insulin resistance by expanding β‐cell mass and enhancing β‐cell function have been shown in rodent models and possibly in humans, although it is uncertain whether a compensatory increase in β‐cell mass undoubtedly exists in humans 3 , 4 , 5 . The strategies to expand the endogenous β‐cell mass include: (i) promoting β‐cell proliferation; (ii) preventing β‐cell death; (ii) inducing β‐cell neogenesis; and (iv) regulating β‐cell transdifferentiation.…”
Section: Introductionmentioning
confidence: 99%